Measurement of Radiation Absorbed Dose Effects in SRAM-Based FPGAs. Issue 5 (3rd September 2022) - Nidhin, T. S.; Bhattacharyya, Anindya; Gour, Aditya; Behera, R. P.; Jayanthi, T.; Velusamy, K.
Abstract : As of now, SRAM-based FPGAs are mainly preferred in the non-safety applications of NPPs. If the susceptibility to radiation effects of SRAM-FPGAs improves further, then the reliability of the applications can be improved. This experimental study investigates the radiation absorbed dose effects in SRAM-based FPGAs. The irradiation experiments have been conducted by keeping the device in both the power-on and power-off states inside a gamma radiation chamber of Co-60 source. In some applications, the device is deployed in the radiation environments and remains in the power-off condition for substantial period. At the time of need, the device may not function properly as demanded by the system due to the cumulative dose effect on SRAM-based FPGA. So the study of irradiation experiments on SRAM-FPGAs in the power-off state has its significant importance the same as the power-on state. The power supply current variation and the functionality failure of the device are monitored in both cases. In the power-on test, the device is configured with particular functionality and the parameters are measured continuously, but in the power-off test, the performance variations of the device are captured after configuring the device at particular time intervals during the course of the experiment. Along with the power supply current variation, we used an indirect method of measuring the propagation delay based on ring oscillator implementation. The device has been irradiated up to a dose level of 2.5 Mrad in power-on test and up to 50 Mrad in the power-off test.